Forest and industry – a symbiosis system - Falencka-Jabłońska, Małgorzata (Studia Ecologiae et Bioethicae, 2018)
The article is a summary of over 40 years’ results in assessment and analysis of chosen components of forest biocoenosis and their adaptation to the accumulation of industrial pollution and growing anthropopressure. These issues were presented in the example context of the impact of the ‘Kozienice’ Power Plant, which is fired with bituminous coal, on the environment of the Kozienice Forest (the largest forest in Poland and, since last year, also in Europe). Those long-term studies were undertaken on permanent experimental areas of the Forest Research Institute before the establishment of the power plant and are still being continued what is a sensation not only on continent level. The second analysis example is the assessment of the long-term impact of Huta Cynku ‘Miasteczko Śląskie’ in the Upper Silesian Industrial Region. Among the discussed components of forest biocoenosis was the differentiation of changes in biodiversity against the backdrop of pollution characteristics and the introduction of pro-ecological technologies in the forest protection field.